India and China: Two Major Higher Education Hubs in Asia - Lavakare, P.J. (International Higher Education, 2018)
Both China and India have large and diverse higher education systems. Students from both countries are keen to enter the global employment market. It is this challenge that demands the respective national education systems produce “global citizens” with the high-quality, diverse, and international educational backgrounds needed on the global market. This article briefly reviews the international education status of India and China and highlights some crucial parameters governing the two systems.